1981
DOI: 10.1093/cvr/15.4.190
|View full text |Cite
|
Sign up to set email alerts
|

Impulse propagation in normal and stenosed vessels

Abstract: The propagation of a transient pressure impulse in a viscoelastic medium was investigated by experiments using water-filled latex rubber tubing and the aorta of anaesthetised dogs. A 5 ms pressure impulse was produced by the impact of a solenoid driven hammer. The propagation characteristics of the impulse (attenuation and propagation velocity) along the vessel were determined by means of a catheter-tip pressure manometer placed at various distances distal to the impulse generator. The presence of stenoses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The results of the renal graft selective angiography were reevaluated: an arteriographic narrowing ≥50% was considered significant for arterial stenosis combined with the clinical history of the patients, as reported by Hagen and Ghazanfar [ 19 , 20 ]. The results validate the mathematical relationship between wall impedance and blood flow disturbances [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 77%
“…The results of the renal graft selective angiography were reevaluated: an arteriographic narrowing ≥50% was considered significant for arterial stenosis combined with the clinical history of the patients, as reported by Hagen and Ghazanfar [ 19 , 20 ]. The results validate the mathematical relationship between wall impedance and blood flow disturbances [ 26 , 27 ].…”
Section: Discussionsupporting
confidence: 77%
“…Previous work on blood wave dissipation includes invitro models and in-vivo measurements including waves in the vena cava [8][9][10][11][12][13][14][15][16][17]. However, although it is widely accepted that measured pressure waveforms consist of the linear summation of the incident and reflected waveforms [18], the majority of previous work investigating wave dissipation used only the measured pressure waveforms [19,20].…”
Section: Background Of Wave Dissipationmentioning
confidence: 99%
“…Anliker et al ( , 1971, Anliker and Maxwell (1968) and Anliker (1974) studied wave dissipation in blood vessels in the frequency domain using wave-trains techniques and found that for the frequency range they considered, the amplitude of waves attenuated exponentially with the distance per wavelengths. Newman et al (1981) also carried out experimental work on wave propagation and found that impulse waves attenuated along the distance travelled as an approximately mono-exponential function in both latex rubber tubes and the aorta of dogs.…”
Section: Introductionmentioning
confidence: 99%